Water and sediment yields from two catchments with different land cover areas - Tyas Mutiara Basuki (Brawijaya University, 2017)
Land cover and human activities affect water yield and soil erosion-sedimentation in a catchment. Therefore, a study to obtain information of water and sediment yields from two catchments covered by different land cover areas has been conducted in Tanjung and Bakar catchments. The catchments are located in Tanah Laut Regency, South Kalimantan Province. The area of secondary forest inTanjung and Bakar catchments are 31 and 10%. The water yield was obtained by measuring Stream Water Level (SWL) and converted the data into stream water discharge using a stream water discharge rating curve. Sediment samples were taken for every increament of SWL. The sediment concentration in water samples were converted to sediment discharge (kg/second) using a sediment discharge rating curve. The results showed that water and sediment yields in 2016 of Tanjung cacthment were higher than Bakar catchment. The water and sediment yields of Tanjung were 2994 mm and 15.7 t/ha. Bakar catchment produces water yield 2750 mm and sediment yield 7.4 t/ha. Based on the study, it shows that the suspended sediment in stream water is not only affected by the percentage of forest cover, but it is also influenced by the activities within the catchment such as traditional mining.